Meta-analysis of the effect of Taijiquan exercise training on the balance ability of middle-aged and elderly of patients with Parkinson's Disease - Sun, Rongkun; Li, Ju; Fang, Yurui; Wu, Zhigui; Hou, Lijuan (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Parkinson's disease is a common neurodegenerative disease in the middle-aged and elderly, with more than 10 million Parkinson's patients worldwide. Parkinson's disease is mainly characterized by dyskinesia. Its clinical manifestations include impaired motor function, accompanied by slow movement, tremor, frozen gait and balance disorder, and obvious muscle strength decline and motor control ability decline. Most patients with Parkinson's disease have gait disorder symptoms. They can't lift their feet normally, which seriously affects the quality of life. With the growth of middle-aged and elderly people, falls are also an adverse event prone to occur in the daily life of middle-aged and elderly patients with Parkinson's disease. Falls and balance disorders have become important research topics to improve the quality of life of the elderly, and they are also urgent problems to be solved in the field of scientific research. Therefore, the development of new physical therapy interventions to reduce movement disorders is very important for the middle-aged and elderly people with Parkinson's disease. Taijiquan is easy to be accepted by the elderly, and is deeply loved by the elderly. This paper will use meta-analysis method to summarize the effect of Taijiquan exercise intervention on the balance ability of middle-aged and elderly Parkinson's patients, so as to provide evidence-based medical basis for the promotion and use of traditional Chinese medicine Taijiquan exercise. Methods: Computer search for PubMed, Web of Science, The Cochrane Library, CNKI, CBM, WanFang Data, VIP Database, etc. All randomized clinical trials (RCT) affecting the balance of PD patients. The search time limit was from the date of publication of each database to JUL. 24, 2021, as well as manual search. According to the Cochrane Handbook 5.1.0 standard, the researcher independently assessed the quality and bias risk of each included document and extracted the data. The remaining 9 literatures were gradually screened through the literature screening flow chart for meta-analysis. The included literatures were meta-analyzed by Stata16 statistical software for heterogeneity, subgroup intervention and funnel diagram. Among them, 7 literatures were of medium quality, and the research was statistically significant. Results: (1) A total of 509 samples were included in the RCT literature. The literature I2 = 93. 9% > 50%, and the P < 0. 1 of Q test suggested that there was strong heterogeneity among the literature selected in this study. Based on the data of this study, it suggested that the source of heterogeneity was inconsistent intervention cycles. Subgroup analysis will be carried out according to the classification of intervention cycles in the follow-up meeting; (2) Long term standardized Taijiquan training for PD patients can not only help to control the symptoms of dyskinesia, but also improve their balance ability and gait and prevent falls; Patients' self-care ability of daily life has been significantly improved, and patients have stronger confidence in activity balance, which fully reflects the advantages and application value of Taijiquan. At the same time, in the process of Taijiquan exercise training, it can enhance the patients to show regular active breathing, exercise the major muscles of the lower limbs, the center of gravity of the human body will continue to move slowly in multiple directions, and obtain body balance by controlling and supporting the relevant body center of gravity. So as to enhance the control ability of core muscle group for body stability; (3) In the Parkinson's rating scale BBS (Berg Balance Scale), it shows that different intervention cycles have different scores compared with the quality scale. The higher the score, the more significant the treatment effect. However, the balance ability shows no significant difference through chart analysis. Conclusion: (1) Taijiquan is a Chinese traditional sports fitness project integrating fitness, self-defense and self-cultivation. Its movements are soft, natural, slow, uniform and coordinated. It is widely popular among the elderly in the community; (2) Long term standardized Taijiquan training for PD patients can not only help to control the symptoms of dyskinesia, but also improve their balance ability and gait and prevent falls; Patients' self-care ability of daily life has been significantly improved, and patients have stronger confidence in activity balance, which fully reflects the advantages and application value of Taijiquan. At the same time, in the process of Taijiquan exercise training, it can enhance the patients to show regular active breathing, exercise the major muscles of the lower limbs, the center of gravity of the human body will continue to move slowly in multiple directions, and obtain body balance by controlling and supporting the relevant body center of gravity. So as to enhance the control ability of core muscle group for body stability; (3) Taijiquan has a certain effect on the balance and exercise ability of patients with early PD, and its intervention effect has a long-term effect, but when this long-term effect is limited, it will gradually decline with the increase of the time when the intervention stops. Traditional exercise Taijiquan can improve the lower limb function of middle-aged and elderly PD patients, but the data on balance ability are not comprehensive. There is no more evidence to prove that Taijiquan is effective on the balance ability of middle-aged and elderly PD patients, In the future research, we should continue to expand the sample size and select enough representative samples for research. If conditions permit, the closed intervention method can be adopted to reduce the impact of external factors as much as possible, and a more perfect intervention scheme can be designed to obtain more objective and accurate research results. Therefore, it is more worthy of clinical application.